Research for Undergraduates; What needs to be done? - Prof Muhammad Idress Anwar, Prof Muhammad Idress Anwar (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
I must start by thanking you for reading this editorial as very few read editorials beyond first three lines. You have this student journal in your hand which is outcome of untiring efforts of many students coupled with guidance from our research team and students research counsel. Let me start from congratulating all that have actively contributed to this journal and research. I have honor to be part of this ostentatious team. It was a difficult task and started by lowering the research bar at undergraduate level. But it has always been a win win story for us. What we witnessed was a great zeal, enthusiasm and passion to develop something outstanding. They are the future post graduate and doctoral scholars and have done a miraculous job.